The Relevance of Forming Tolerance of Future Lawyers - Nadiia Yashyn (Vasyl Stefanyk Precarpathian National University, 2017)
The article is devoted to the study of the relevance of tolerance formation of law students. The analysis of the scientific and pedagogical literature on the problem is conducted. The article examines the  meaning of the concept of "tolerance". The factors influencing the formation of a tolerant personality are identified. The author emphasizes the need for and efficacy of fostering tolerance in the process of studying at higher educational institutions. The student age is considered to be the most favourable period for the development of the student's personality and his worldview. The paper characterizes the role of lawyers in the society. The place of tolerance in the system of humanistic values of a lawyer is discussed. The importance of this quality for his professional activity is justified. The examples of intolerant behaviour of legal professionals are shown. The tasks and skills of a lawyer necessary for the effective legal practice are determined. Key words: tolerance, tolerant personality, student age, higher education, lawyer, education.